Male violence or patriarchal violence? Global Trends in Men and Violence - Gary Barker
Abstract Policies and research have focused recently on men's use of violence against women, and the terms "gender-based violence" or "domestic violence" have often been used rather than "patriarchal violence." This article argues that instead of talking about "male violence," or gender-based violence, a more useful analytical framework is "patriarchal violence." Applying this lens examines how violence is based in complex power relations - with low-income men and men in specific groups, such as indigenous men or men of socially excluded ethnic groups, experiencing it more at the hands of more powerful men. The article argues for moving beyond a simplistic repressive model of violence prevention that often ignores structural inequalities, to one that understands intersectionalities and multiple power dimensions while also taking into account power dimensions of men's violence against women.